Antistatic silicone oil material, and preparation method and application thereof
By designing antistatic silicone oil materials containing polysiloxane main chains and polyether side chains, and chemically bonding the terminal vinyl groups into the VMQ silicone matrix, the problems of inorganic filler agglomeration and organic additive migration are solved, achieving long-lasting antistatic performance and good processing performance, making it suitable for high-end electronics and new energy fields.
Patent Information
- Application Number
- CN202610879308.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-06-17
AI Technical Summary
Existing VMQ silica gel antistatic modification methods suffer from problems such as easy agglomeration and poor dispersibility of inorganic conductive fillers, which increases the viscosity of the system and makes processing difficult. In addition, organic antistatic additives have poor compatibility, are prone to migration and precipitation, and lead to rapid decay of antistatic performance, affecting their application in high-end fields.
Design an antistatic silicone oil material containing a polysiloxane backbone and polyether side chains, with terminal vinyl groups, adapted to VMQ peroxide and addition systems, and firmly embedded in a silicone matrix through chemical bonding to improve compatibility and antistatic properties.
It effectively extends the service life of antistatic properties, improves processing performance, maintains the original flexibility and temperature resistance of silicone, and enhances the adhesion and surface hydrophilicity of the material, making it suitable for high-end fields such as electronics, new energy and precision instruments.
Smart Images

Figure CN122404708B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, and particularly relates to an antistatic silicone oil material, its preparation method and application. Background Technology
[0002] Vinyl methyl silicone rubber (VMQ) possesses excellent high and low temperature resistance, flexibility, electrical insulation, and good processability, making it widely used in high-end fields such as precision electronic manufacturing, semiconductor packaging, new energy equipment, and precision instrument protection. However, VMQ silicone rubber has a high resistivity, making it prone to generating and accumulating static electricity during production, storage, transportation, and use. This not only attracts dust and causes surface contamination of products but also easily triggers electrostatic discharge, leading to breakdown of precision components and equipment failure. In flammable and explosive environments, it poses significant safety hazards, severely limiting its high-end applications. Therefore, long-term antistatic modification of VMQ silicone rubber has become a key research focus in this field.
[0003] Currently, the antistatic modification of VMQ silicone in the industry mainly involves the doping of inorganic conductive fillers and the compounding of small / large molecule organic antistatic additives. However, all of the above modification methods have obvious technical defects. Inorganic carbon-based and metal-based conductive fillers are prone to agglomeration and poor dispersibility, which will destroy the original mechanical and flexible properties of silicone, increase the viscosity of the system, increase the processing difficulty, and have high filling thresholds and high production costs. Organic antistatic additives containing polyether chains and ionized structures have poor compatibility with the low polarity of the VMQ matrix and are prone to phase separation during vulcanization / crosslinking. The additives are prone to migration to the surface and precipitation, resulting in a rapid decline in the antistatic performance of the product. Furthermore, the introduction of reactive groups such as Si-H bonds into organic antistatic additives can also cause undesirable side reactions during crosslinking due to the high activity of Si-H bonds, resulting in a decrease in the overall mechanical properties of the product.
[0004] Therefore, how to provide an antistatic VMQ material that has both excellent antistatic and mechanical properties is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of the existing technology, this invention provides an antistatic silicone oil material, its preparation method, and its applications. The molecular structure of this antistatic silicone oil material is precisely designed, possessing a polysiloxane backbone, polyether side chains, and terminal vinyl groups. It is compatible with both VMQ peroxide and addition systems, effectively overcoming the limitations of existing technologies and possessing high industrial application value.
[0006] The purpose of this invention is to provide an antistatic silicone oil material, the structural formula of which is shown in formula (Ⅰ):
[0007] Equation (Ⅰ);
[0008] R1 is selected from alkylene groups having 1 to 3 carbon atoms, and R2 and R3 are independently selected from alkyl groups having 1 to 3 carbon atoms.
[0009] For the aforementioned antistatic silicone oil materials, firstly, the polysiloxane backbone is compatible with the VMQ system, which is beneficial for processing and maintaining performance stability; secondly, silicone oil materials containing terminal vinyl groups are relatively stable, with good storage and processability, and the terminal vinyl groups can participate in the polymerization reaction of the VMQ system, achieving stable chemical bonding into the silicone matrix in both peroxide and addition systems without negatively affecting the properties of the silicone matrix itself. This not only solves the problem of additive loss and significantly extends the service life of antistatic agents, but also solves the problem of performance degradation of the silicone system due to the introduction of antistatic agents; thirdly, the polyether side chains with a certain polarity tend to accumulate on the surface of the material during vulcanization / crosslinking, improving surface hydrophilicity and wet conductivity, which not only improves the adhesion of the material, but also stably endows the VMQ material with excellent long-term antistatic properties.
[0010] Preferably, m, n, and k in structural formula (Ⅰ) are independently selected from any integer from 3 to 200.
[0011] More preferably, m is selected from any integer from 3 to 60, even more preferably from any integer from 3 to 30, and most preferably from any integer from 3 to 8.
[0012] More preferably, n is selected from any integer from 5 to 200, even more preferably from any integer from 5 to 100, and most preferably from any integer from 5 to 10.
[0013] More preferably, k is selected from any integer from 3 to 50, even more preferably from any integer from 3 to 20, and most preferably from any integer from 5 to 10.
[0014] More preferably, the ratio of m to n, m:n, is 0.01 to 0.3:1, and even more preferably, it is 0.1 to 0.2:1.
[0015] Preferably, the viscosity of the antistatic silicone oil material is 500~3000 mPa·s, for example, it can be 800 mPa·s, 1000 mPa·s, 1200 mPa·s, 1500 mPa·s, 1800 mPa·s, 2000 mPa·s or 2500 mPa·s.
[0016] In this invention, controlling the values of m, n, or k, or the ratio of m:n, or the viscosity preferably within the above range, is beneficial for obtaining better / longer-lasting antistatic properties.
[0017] Another object of the present invention is to provide a method for preparing the above-mentioned antistatic silicone oil material, characterized by comprising the following steps:
[0018] S1. A mercaptoalkyldialkoxysilane and ethylene oxide undergo an epoxide ring-opening reaction to yield compound A; wherein the structural formula of the mercaptoalkyldialkoxysilane is shown in formula (II):
[0019] Formula (II); wherein R4 and R5 are independently selected from alkyl groups having 1 to 3 carbon atoms;
[0020] S2. Compound A is polymerized with octamethylcyclotetrasiloxane and vinyl monoalkoxysilane to obtain the antistatic silicone oil material; wherein the vinyl monoalkoxysilane has the structural formula shown in Formula (III):
[0021] Formula (Ⅲ); wherein R6 is selected from alkyl groups having 1 to 3 carbon atoms.
[0022] It is understandable that the compound A obtained from S1 above has the structural formula shown in formula (Ⅳ):
[0023] Formula (Ⅳ).
[0024] Furthermore, the reaction formula for S1 above is:
[0025] .
[0026] Furthermore, the reaction formula for S2 above is:
[0027]
[0028] Preferably, in S1, the molar ratio of the mercaptoalkyldialkoxysilane to the ethylene oxide is 1:3 to 50, more preferably 1:3 to 20, and most preferably 1:5 to 10.
[0029] Preferably, the mercaptoalkyldialkoxysilane is selected from at least one of mercaptopropyldimethoxymethylsilane, mercaptopropyldiethoxymethylsilane, mercaptopropyldimethoxyethylsilane, and mercaptopropyldiethoxyethylsilane.
[0030] Preferably, in S1, the epoxy ring-opening reaction is carried out under conditions of anhydrous and oxygen-free environment and containing an alkaline catalyst.
[0031] Preferably, the alkaline catalyst is selected from at least one of potassium hydroxide, sodium hydroxide, and triethylamine.
[0032] Preferably, the amount of alkaline catalyst used is 0.5 to 5 wt% of the ethylene oxide.
[0033] Preferably, in S1, the temperature of the epoxy ring-opening reaction is 50~60℃ and the time is 3~6h.
[0034] Preferably, in step S1, after the epoxy ring-opening reaction is completed, the steps of adding an acidic compound to neutralize the pH of the system, filtering, and drying are further included.
[0035] Preferably, the acidic compound is selected from at least one of hypophosphorous acid and phosphoric acid.
[0036] Preferably, in S2, the molar ratio of compound A, octamethylcyclotetrasiloxane, and vinylmonoalkoxysilane is 3~60:5~200:2, more preferably 3~30:5~100:2, and most preferably 3~8:5~10:2.
[0037] And / or, in S2, the polymerization reaction is carried out under conditions containing a polymerization inhibitor and a condensation catalyst.
[0038] And / or, in S2, the polymerization reaction is carried out at a temperature of 100~120℃ for a time of 4~8h.
[0039] Preferably, the polymerization inhibitor is selected from at least one of MEHQ, BHT, phenothiazine, and hydroquinone.
[0040] Preferably, the amount of the polymerization inhibitor is 0.01~1 mol of the vinyl monoalkoxysilane.
[0041] Preferably, the condensation catalyst is selected from at least one of tetramethylammonium hydroxide and benzyltrimethylammonium hydroxide.
[0042] Preferably, the amount of the condensation catalyst is 0.02~0.2 mol of the octamethylcyclotetrasiloxane.
[0043] Another object of the present invention is to provide the application of the above-mentioned antistatic silicone oil material or the antistatic silicone oil material obtained by the above-mentioned preparation method in the preparation of antistatic VMQ material.
[0044] Preferably, the antistatic silicone oil material has a mass percentage of 5-20% in the antistatic VMQ material, for example, 8%, 10%, 12%, 15% or 18%.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The antistatic silicone oil material of the present invention has a scientific and reasonable molecular structure design. The terminal active silicone vinyl group is not only suitable for peroxide system, but also suitable for hydrosilylation system. It has strong universality and can have better application value in industry.
[0047] (2) The terminal active silicone vinyl group contained in the antistatic silicone oil material of the present invention, on the basis of good stability, can also participate in the polymerization reaction in the VMQ silicone matrix and be firmly embedded in the silicone cross-linking network through chemical bonding. This overcomes the disadvantages of traditional small molecule antistatic additives that are easy to migrate, precipitate and lose, and solves the problem of the decay of antistatic performance of the product from the root. It effectively guarantees and extends the service life of the antistatic performance of VMQ silicone, and will not have a negative impact on the properties of the silicone matrix itself, such as adhesion.
[0048] (3) The antistatic silicone oil material of the present invention has a high homology and excellent compatibility with the VMQ silicone matrix structure of its siloxane main chain. It can be uniformly dispersed in the system, which can effectively improve the defects of traditional inorganic conductive fillers that are easy to agglomerate, have high system viscosity and high processing difficulty. It can achieve excellent modification effect without high filling amount. The production and processing process is simple and will not damage the excellent flexibility and temperature resistance of silicone itself, and fully retain the original excellent properties of the substrate.
[0049] (4) The long-chain polyoxyethylene polar structure contained in the antistatic silicone oil material of the present invention tends to spontaneously accumulate on the surface of the product during the silicone vulcanization / crosslinking process. This not only helps to improve the adhesion of the material, but also helps to improve the hydrophilicity and moisture absorption conductivity of the silicone surface, quickly dissipate the surface static electricity, and stably endow the product with excellent surface antistatic properties.
[0050] In summary, the antistatic silicone oil material of this invention has low modification cost, wide system adaptability, and stable comprehensive performance, which can fully meet the long-term use needs of high-end fields such as electronics, new energy, and precision instruments, and has good application prospects and industrial promotion value. Detailed Implementation
[0051] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0052] Unless otherwise specified, all raw materials used in this invention are commercially available.
[0053] Example 1
[0054] This embodiment provides an antistatic silicone oil material M1, the preparation method of which includes the following steps:
[0055] S1. In an anhydrous and oxygen-free pressure-resistant reactor, 1 mole of 3-mercaptopropylmethyldimethoxysilane (pre-treated with molecular sieves and dried), 5 moles of ethylene oxide (weighed in an ice bath), and 1.5 wt% sodium hydroxide (the alkaline catalyst of ethylene oxide) were added. The system was heated and the reaction temperature was controlled at 60 ± 2 °C for 3 h. After the reaction was completed, the mixture was neutralized with phosphoric acid, adsorbed with aluminum oxide, filtered, and dried to obtain compound A1-5EO.
[0056] S2. Under a nitrogen atmosphere, compound A1-5EO (0.8 mol), octamethylcyclotetrasiloxane D4 (1.6 mol), vinyldimethylmethoxysilane (0.4 mol), and hydroquinone (0.1 mol% of vinyldimethylmethoxysilane) were added to a reaction vessel. The system was heated to 60-70°C and stirred for 15 minutes, then heated to 80°C and vacuumed to remove water for 0.5 hours. After that, the condensation catalyst benzyltrimethylammonium hydroxide (0.05 mol% of D4) was added. A nitrogen:air gas ratio of 3:1 (v / v) was introduced into the reaction flask. The reaction temperature was raised to 110±2°C and reacted for 5 hours. Then, the temperature was lowered to 90°C and vacuumed to remove low-boiling substances, finally obtaining a clear and transparent antistatic silicone oil material M1.
[0057] Example 2
[0058] This embodiment provides an antistatic silicone oil material M2, which differs from Example 1 only in the amount of ethylene oxide in S1. Specifically, in this embodiment, the amount of ethylene oxide is 10 moles. Everything else remains the same as in Example 1.
[0059] Example 3
[0060] This embodiment provides an antistatic silicone oil material M3, which differs from Example 1 only in the amount of ethylene oxide used in S1. Specifically, in this embodiment, the amount of ethylene oxide is 15 molar parts. Everything else remains the same as in Example 1.
[0061] Example 4
[0062] This embodiment provides an antistatic silicone oil material M4, which differs from Example 1 only in the amount of octamethylcyclotetrasiloxane D4 used in S2. Specifically, in this embodiment, octamethylcyclotetrasiloxane D4 is 10 molar parts. Everything else remains the same as in Example 1.
[0063] Comparative Example 1
[0064] This comparative example provides an antistatic silicone oil material M5, which differs from Example 1 only in the end-capping agent in S2 and does not contain the polymerization inhibitor hydroquinone. Specifically, the steps in S2 of this comparative example are as follows:
[0065] S2. Under a nitrogen atmosphere, compound A1-5EO (0.8 mol), octamethylcyclotetrasiloxane D4 (1.6 mol), and hexamethyldisiloxane (0.2 mol) were added to a reactor. The system was heated to 60-70°C and stirred for 15 minutes, then heated to 80°C and vacuumed to remove water for 0.5 hours. Afterward, the condensation catalyst benzyltrimethylammonium hydroxide (0.05 mol% of D4) was added. A nitrogen:air ratio of 3:1 (v / v) was introduced into the reaction flask, and the reaction was heated to 110±2°C for 5 hours. Then, the temperature was lowered to 90°C and vacuumed to remove low-boiling-point substances, finally yielding a clear and transparent antistatic silicone oil material M5. This antistatic silicone oil material M5, compared to M1, does not contain vinyl groups at the ends.
[0066] Comparative Example 2
[0067] This comparative example provides an antistatic silicone oil material M6, the preparation method of which is as follows:
[0068] S1. Under a nitrogen atmosphere, add 0.8 mol of octamethylcyclotetrasiloxane D4, 0.05 mol of tetramethylcyclotetrasiloxane D4H, and 0.05 mol of hexamethyldisiloxane to a reaction vessel. Heat the system to 60-70°C and stir for 15 minutes. Then, heat the system to 80°C and remove water under vacuum for 0.5 hours. After that, add the condensation catalyst benzyltrimethylammonium hydroxide (0.05 mol% of D4). Purge the reaction vessel with a nitrogen:air ratio of 3:1 (v / v). Heat the reaction vessel to 110±2°C and react for 5 hours. Then, cool the reaction vessel to 90°C and remove low-boiling substances under vacuum to obtain hydrogen-containing silicone oil.
[0069] S2. Add 0.1 mol of allyl polyoxyethylene ether (number average molecular weight 400) and a platinum catalyst (chloroplatinic acid, 0.1 mol% of allyl polyoxyethylene ether) to the hydrogen-containing silicone oil obtained in S1. After heating the system to 110°C for 4 hours, cool down to obtain antistatic silicone oil material M6. Compared with M1, this antistatic silicone oil material M6 does not contain vinyl groups at the end and contains silane-hydrogen bonds in its structure, that is, it is a hydrogen-containing silicone oil with polyoxyethylene ether segments branched on the sides.
[0070] Application Example 1
[0071] This application example provides a series of antistatic VMQ materials based on a peroxide system, the preparation method of which includes the following steps, by weight:
[0072] In a system of 100 parts VMQ resin and 1 part thermal initiator BPO, 10 parts of compounds M1-5 obtained in Examples 1-4 and Comparative Example 1 were added and mixed evenly. The mixture was then coated onto a tinplate with a thickness of about 0.2 mm and placed in a flat vulcanizing machine. The temperature was raised to 150°C for reaction and cross-linking molding to obtain VMQ materials A-E, with the thickness of the antistatic coating being about 0.05 mm.
[0073] Application Example 2
[0074] This application example provides a series of antistatic VMQ materials based on the hydrosilylation system, which are prepared by the following steps, by weight:
[0075] In 90 parts of VMQ resin and 10 parts of hydrogen-containing silicone oil with a hydrogen content of 0.1 wt%, 10 parts of compounds M1-5 obtained in Examples 1-4 and Comparative Example 1, and 50 ppm of Pt catalyst were added respectively. The mixture was coated onto a tinplate with a thickness of about 0.2 mm and then placed in a flat vulcanizing machine. The temperature was raised to 110 °C for reaction and cross-linking molding to obtain VMQ materials F-J, respectively, wherein the thickness of the antistatic coating is about 0.05 mm.
[0076] Application Example 3
[0077] This application example provides a series of antistatic VMQ materials based on the hydrosilylation system, which are prepared by the following steps, by weight:
[0078] In 100 parts of VMQ resin, 10 parts of compound M6 obtained in Comparative Example 2 above and 50 ppm of Pt catalyst were added. The mixture was coated onto a tinplate with a thickness of about 0.2 mm and then placed in a flat vulcanizing machine. The temperature was raised to 110 °C for reaction and cross-linking molding to obtain VMQ material K, in which the thickness of the antistatic coating is about 0.05 mm.
[0079] The following performance tests were conducted on VMQ materials A~K, and the test results are shown in Table 1.
[0080] Antistatic properties: On the one hand, the initial surface resistance of the antistatic coating of VMQ material was tested; on the other hand, after rubbing the surface of VMQ material with an eraser 500 times under a 1kg load, its surface resistance after friction was measured and its rate of change relative to the initial surface resistance was calculated.
[0081] Flexibility: VMQ material was bent around shafts of different diameters (2, 3, 4, 5, 6, 8, 10, 12, 16, 18, 20, 25, 32 mm), and the presence of cracking or peeling of the coating was visually observed. The smallest diameter at which no cracking or peeling occurred was recorded. The smaller the smallest diameter, the better the flexibility.
[0082] Adhesion: After placing the VMQ material in a double 85 environment for 500 hours, the adhesion of the VMQ material was tested using the cross-cut test.
[0083] Table 1: Performance of different antistatic VMQ materials
[0084]
[0085] As shown in Table 1, the antistatic silicone oil materials M1-4 with polyether side chains and vinyl end groups obtained in Examples 1-4 of the present invention, compared with the antistatic silicone oil material M5 without vinyl end groups prepared in Comparative Example 1, or the antistatic silicone oil material M6 without vinyl end groups but with silane-hydrogen bonds prepared in Comparative Example 2, have lower initial surface resistance and surface resistance after friction, good flexibility and adhesion. That is, they have excellent antistatic properties, antistatic friction stability, flexibility and adhesion.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that after reading this application specification, they can still modify or make equivalent substitutions to the specific implementation of the present invention, but these modifications or changes do not depart from the protection scope of the pending claims of the present invention.
Claims
1. An antistatic silicone oil material, characterized in that, The structural formula is shown in equation (Ⅰ): Equation (Ⅰ); Wherein, R1 is selected from alkylene groups having 1 to 3 carbon atoms, and R2 and R3 are independently selected from alkyl groups having 1 to 3 carbon atoms; The m is selected from any integer from 3 to 60, the n is selected from any integer from 5 to 200, and the ratio of m to n, m:n, is 0.01 to 0.3:
1. The k is selected from any integer from 3 to 50.
2. The antistatic silicone oil material as described in claim 1, characterized in that, The k is selected from any integer from 5 to 10; and / or the ratio of the m to the n is 0.1 to 0.2:
1.
3. The antistatic silicone oil material as described in claim 1, characterized in that, The viscosity of the antistatic silicone oil material is 500~3000 mPa·s.
4. The method for preparing the antistatic silicone oil material according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. A mercaptoalkyldialkoxysilane and ethylene oxide undergo an epoxide ring-opening reaction to yield compound A; wherein the structural formula of the mercaptoalkyldialkoxysilane is shown in formula (II): Formula (II); wherein R4 and R5 are independently selected from alkyl groups having 1 to 3 carbon atoms; S2. Compound A is polymerized with octamethylcyclotetrasiloxane and vinyl monoalkoxysilane to obtain the antistatic silicone oil material; wherein the vinyl monoalkoxysilane has the structural formula shown in Formula (III): Formula (Ⅲ); wherein R6 is selected from alkyl groups having 1 to 3 carbon atoms.
5. The preparation method according to claim 4, characterized in that, In S1, the molar ratio of the mercaptoalkyldialkoxysilane to the ethylene oxide is 1:3~50; And / or, the epoxy ring-opening reaction is carried out under anhydrous and oxygen-free conditions and with a basic catalyst; And / or, the epoxy ring-opening reaction is carried out at a temperature of 50-60°C for a time of 3-6 hours; And / or, after the epoxy ring-opening reaction is completed, the process further includes adding an acidic compound to neutralize the pH of the system, filtering, and drying.
6. The preparation method according to claim 4, characterized in that, In S2, the molar ratio of compound A, octamethylcyclotetrasiloxane, and vinyl monoalkoxysilane is 3~60:5~200:2; And / or, the polymerization reaction is carried out under conditions containing a polymerization inhibitor and a condensation catalyst; And / or, the polymerization reaction is carried out at a temperature of 100~120℃ for a time of 4~8h.
7. The preparation method according to claim 6, characterized in that, The polymerization inhibitor is selected from at least one of MEHQ, BHT, phenothiazine, and hydroquinone; And / or, the amount of the polymerization inhibitor is 0.01 to 1 mol of the vinyl monoalkoxysilane.
8. The preparation method according to claim 6, characterized in that, The condensation catalyst is selected from at least one of tetramethylammonium hydroxide and benzyltrimethylammonium hydroxide; And / or, the amount of the condensation catalyst is 0.02~0.2 mol of the octamethylcyclotetrasiloxane.
9. The application of the antistatic silicone oil material according to any one of claims 1 to 3 or the antistatic silicone oil material obtained by the preparation method according to any one of claims 4 to 8 in the preparation of antistatic VMQ materials.
10. The application as described in claim 9, characterized in that, The antistatic silicone oil material accounts for 5-20% of the mass percentage of the antistatic VMQ material.
Citation Information
Patent Citations
Polyorganosiloxane / polyvinyl-based graft polymers, process and thermoplastic compositions containing the same
CA2039134A1
Block type amino polyether modified silicone oil and preparation method thereof
CN102250358A
